Perbandingan Variasi Window Level Terhadap Spatial Resolution dan Contrast Resolution CT Scan Thorax dengan Kasus Tumor Paru - Dewilza, Nerifa; Yudha, Sagita; Sari, Oktavia Puspita; Febriyani, Putri Wirya (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
CT Scan is an imaging modality that combines X-rays using the principles of Tomography with a computer as the data processor. Lung Window settings for CT Scan Thorax examination use Window level -500 HU. In the Radiology Installation of Dr. M. Djamil Padang Hospital, CT Scan Thorax examination uses Window level - 600 HU. This study aims to determine which Window level value is better from the variation of Window level values on the lung window - 400 HU, - 500 HU, and - 600 HU on the quality of CT Scan Thorax images with Lung Tumor cases on the Lung Window axial section. The type of research used in this study is quantitative research that is experimental. This research was conducted in the Radiology Installation of Dr. M. Djamil Padang Hospital. The population of this study were patients with CT Scan Thorax examinations with clinical Lung Tumors. The sample in this study amounted to 5 patients with a purposive sampling technique. Then the image results are varied using Window Level value variations - 400 HU, - 500 HU, and - 600 HU and then compared to see which Window Level variation produces optimal image quality. The best value that can display optimal image quality is the window level value of -600 HU because it can show the lung hilus and show pathology in detail and can display a better level of brightness in the image.